Raw Defines a Distinct TIR-fold cADPR Hydrolase Family and Cooperates with dSarm in Development and Axon Degeneration - Chen, Feng; Chen, Zhuo; Tan, Yongjun; Shen, Xin Ye; Leong, Matthew; Yang, Jian Yuan; Li, Wan Hua; Hou, Yun Nan; Bao, Guo; Chen, Yue Jun; Ma, Yu Ran; Chan, Ting-Fung; et al. (LangTaoSha Preprint Server, 2025)
Conserved TIR domain proteins play essential roles in immune signaling, development, and neurodegeneration. Here, we identify Raw as a member of a distinct TIR protein family that functions as a cADPR-specific hydrolase, with catalytic mutations phenocopying delayed axon degeneration. While Raw and dSarm synergistically deplete NAD to drive axon degeneration, they antagonistically regulate cADPR levels in S2 cells, modulating development-related genes via the Ask1/JNK pathway, a non-canonical cADPR signaling mechanism independent of calcium mobilization. Consistently, Raw knockdown in fly wing discs elevates JNK phosphorylation, alters developmental gene expression, and causes wing defects, all rescued by Ask1 knockdown. Similarly, dSarm overexpression induces pupal lethality, which is also reversed by Ask1 suppression. Phylogenetic analysis reveals the co-evolution of dSarm and Raw across species, with conserved cADPR-hydrolysis activity observed in C. elegans Olrn-1. These findings underscore the distinct yet cooperative roles of dSarm and Raw in cADPR signaling-mediated development and NAD depletion-driven axon degeneration.